I dont have any idea how to start this equation.
$\displaystyle ln(x^2-1) + 2ln(2) = ln (4x -1)$
How can i simplify this equation??
(sorry my english)
So: $\displaystyle ln(x^2-1) + 2ln(2) = ln (4x -1)$
$\displaystyle ln(x^2-1) + ln(4) = ln (4x -1)$
$\displaystyle ln ((x^2-1)4)) = ln(4x -1)$
$\displaystyle ln ((4x^2-4)) = ln (4x-1)$
$\displaystyle ln ((4x^2-4)) - ln (4x-1) = 0 $
$\displaystyle ln ((\frac{4x^2-4}{4x-1})) = 0$
$\displaystyle \frac{4x^2-4}{4x-1} = e^0$
$\displaystyle 4x^2-4 = 4x-1$ ?